Use of mineral additives in the production of meat products - Ivanov, Sergey; Pasichnyi, Vasyl; Olishevskyi, Valentyn; Marynin, Andriy; Tymoshenko (Kremeshna), Irina (My University, 2013)
Lately in the group of texturizing food additives a great emphasis is placed on stabilizing systems consisting of several components. We determined the optimal composition of composite mixtures of factorial experiments, color using chromaticity scale, moisture-binding capacity and flexibility of mixtures pressing method using and thermal stability of beet dye by heating at different temperatures, ξ-potential of the dye solutions with nutritional supplements. The research allowed to determine the rational composition of a model mixtures based nanocomposites and developed a red dye from beets for stabilizing technological, structural and mechanical properties of meat products and groups containing meat, meat bread. The possibility was confirmed to stabilize ξ potential of beet juice by adding buffer compound and mineral additive, as well as a viable potential for applying such compositions in production of meats and processed meats manufactured using the cooked sausage and meat loaf technology. В останні роки в групі харчових добавок, які регулюють консистенцію, велика увага приділяється стабілізаційним системам, які містять декілька компонентів. Визначали оптимальний склад композиційних сумішей за факторним експериментом, колір за шкалою «Тінторама», волого-зв'язуючу здатність та пластичність сумішей методом пресування, а також термостійкість розробленого нами бурякового барвника методом нагрівання при різних температурах, ξ-потенціал розчинів барвника з харчовими добавками. Проведені дослідження дозволили визначити раціональний склад структуро-моделюючих композиції на основі нанокомпозитів і розробленого червоного барвника з буряку. Підтверджена можливість стабілізації ξ-потенціалу бурякового соку буферним комплексом і мінеральною добавкою, перспективність використаня даних композитів у технології виробництва м'ясних та м'ясомістких продуктів, що виробляються за технологіями виробництва варених ковбас і м'ясних хлібів.
Keywords: meat and containing meat products; dye; color; stabilization; nanocomposites; quality; м'ясомпродукти; барвник; стабілізація; нанокомпозити; якість; кафедра технології м’яса і м’ясних продуктів; кафедра технологічного обладнання та комп’ютерних технологій проектування; кафедра експертизи харчових продуктів